Comparison of Visual Acuity and Astigmatic Changes in Phacoemulsification with Posterior Chamber Foldable Vs Non Foldable Intraocular Lens Implant - Zafar Iqbal, Mohammad Alam (Pakistan Journal of Ophthalmology, 2007)
Purpose: To compare visual acuity and astigmatic changes in phacoemulsification with posterior chamber foldable versus non-foldable IOL implants. Materials and Methods: This comparative study was conducted in the Ophthalmology Department of Khyber Teaching Hospital, Peshawar from January 2001 to June 2002. We selected 50 patients with age related cataract and divided them into two groups A & B, each comprising of 25 patients. All of these patients underwent cataract removal by phacoemulsification. In group-A, foldable posterior chamber IOL while in group-B, non foldable posterior chamber IOL were implanted in the bag. Visual acuity and astigmatic changes were recorded on first post operative day, end of first week and at the end of first month. Results: At the end of first month, in group-A, 84% of patients had best corrected visual acuity of 6/6 and 16% of patients had 6/9. In group-B, 80% of patients had best corrected visual acuity of 6/6, 16% had 6/9 while 4% had 6/12. At the end of first month, in group-A, 92% of patients had astigmatism between 0 – 0.9D and 8% had 1 – 1.9D. In group-B, 76% of patients had astigmatism between 0 – 0.9D, 16% had 1 – 1.9D while 8% had 2 –2.9D. Conclusions: In both groups, visual acuity is comparable, however astigmatic changes are more in the non-foldable IOL’s as compared to the foldable IOL’s group.